Establishing Consumer Trust Through Data Protection Law as a Competitive Advantage in Indonesia and India - Prastyanti, Rina Arum; Sharma , Ridhima (Journal of Human Rights, Culture and Legal System, 2024)
Data protection laws play a crucial role in enhancing consumer trust in the digital economy, especially with the rise of online cybersecurity threats due to firm expansion. Despite advances, personal data protection laws remain controversial globally, with challenges in implementation hindering progress in some regions. This research examines the competitive advantage of building consumer trust through the Personal Data Protection Law. This research uses juridical-normative research with a legislative approach and comparison with other countries. A comparison was made with India, one of the countries with higher awareness of the importance of personal data protection laws than other countries. The results show that Consumer trust in a company is measured by the extent to which they believe the company will protect their data. Public privacy policies and government regulations that enforce data security measures and increase transparency positively impact trust by reducing concerns about privacy risks. Although data protection laws have been introduced, obstacles such as lack of legal assistance and overlapping sectoral regulations still exist, hindering the smooth implementation of these laws. Nevertheless, implementing data protection laws, such as Indonesia's Private Data Protection Law No. 27 of 2022 and India's Digital Personal Data Protection Act of 2023, is crucial for boosting consumer confidence and regulating data processing. Data security is critical in establishing and maintaining consumer trust in companies as online cybersecurity threats increase with business expansion.